Expansion of aquaculture threatens the existence of wetlands in Bangladesh - Md. Taskin Parvez; ABM Mohsin (Journal of Fisheries, 2022)
Despite positive role of aquaculture in food production, the practice may impact the environment negatively and it is difficult to quantify the loss. In this study, we assessed land use changes in four important wetlands (Hardoho Beel, Angrar Beel, Shaoil Beel and Gopalpur Beel) of Bangladesh through analysis of historical satellite images (1990 – 2020) to show how expansion of aquaculture activities threatens the existence of freshwater wetlands. Since 1990, the water area of all four wetlands decreased significantly over time (all p < 0.001). Mean yearly loss of 47.9 ± 79.3 ha, 99.2 ± 185.5 ha, 51.2 ± 61.9 ha and 2.6 ± 4.7 ha were recorded for Hardoho Beel, Angrar Beel, Shaoil Beel and Gopalpur Beel respectively. A decreasing trend in wetland area was recorded in all wetlands, primarily due to excavation of aquaculture ponds. In 2020, aquaculture ponds represented 72% of the core wetland areas. Two wetlands (Hardoho and Gopalpur) were almost totally lost and converted to aquaculture ponds and agricultural lands. This study concludes that the existence of freshwater wetlands in Bangladesh is at stake and recommends further studies to determine its impacts on people's livelihood and biodiversity.